The association of early diarrhea after successful resuscitation following out-of-hospital cardiac arrest with neurological outcome: A retrospective observational study. Issue 49 (10th December 2021) - Schriefl, Christoph; Steininger, Philipp; Clodi, Christian; Mueller, Matthias; Poppe, Michael; Ettl, Florian; Nuernberger, Alexander; Grafeneder, Juergen; Losert, Heidrun; Schwameis, Michael; Holzer, Michael; Sterz, Fritz; et al.
Abstract : Abstract: Gastrointestinal ischemia with reperfusion tissue injury contributes to post-cardiac arrest syndrome. We hypothesized that diarrhea is a symptom of intestinal ischemia/reperfusion injury and investigated whether the occurrence of early diarrhea (≤12 hours) after successful cardiopulmonary resuscitation is associated with an unfavorable neurological outcome. We analyzed data from the Vienna Clinical Cardiac Arrest Registry. Inclusion criteria comprised ≥18 years of age, a witnessed, non-traumatic out-of-hospital cardiac arrest, return of spontaneous circulation (ROSC), initial shockable rhythm, and ST-segment elevation in electrocardiogram after ROSC with consecutive coronary angiography. Patients with diarrhea caused by other factors (e.g., infections, antibiotic treatment, or chronic diseases) were excluded. The primary endpoint was neurological function between patients with or without "early diarrhea" (≤12 hours after ROSC) according to cerebral performance categories. We included 156 patients between 2005 and 2012. The rate of unfavorable neurologic outcome was higher in patients with early diarrhea (67% vs 37%). In univariate analysis, the crude odds ratio for unfavorable neurologic outcome was 3.42 (95% confidence interval, 1.11–10.56, P  = .03) for early diarrhea. After multivariate adjustment for traditional prognostication markers the odds ratio of early diarrhea was 5.90 (95% confidence interval, 1.28–27.06, P  = .02). In conclusion, early diarrhea within 12 hours after successful cardiopulmonary resuscitation was associated with an unfavorable neurological outcome.